Thermal comfort studies on houses in hot arid climates - Hj Mohd Ariffin, Noor Aziah; Behaz, Amira; Denan, Zuraini (Institute of Physics Publishing, 2018)
The traditional houses in Ghardaia City in Algeria had been built using traditional construction materials and passive solar design (PSD) strategies for the hot desert climate. These thousand-year-old houses are still standing and conditioning the harsh desert climate while maintaining indoor thermal comfort for its occupants. Of late, two trends of modern housing and construction were observed to have evolved in Ghardaia. Firstly, were the modern houses (Mod.H) following the international style and secondly, the eco-friendly houses (Eco.H), modern houses but utilising passive solar design. The Mod.H was observed to implement some of the traditional features but using the modern construction material. Meanwhile, the Eco.H modified the characteristics of the traditional construction and materials carefully in a modern context. Analyses were conducted to investigate the thermal performances of the three house designs. The intention was to ascertain the best construction that can achieve and maintain thermal comfort according to ANSI-ASHRAE 2014, in this harsh desert climate. Based on the Trad.H model, comfort data the two more modern houses were also monitored. Data collection was carried out in July, which was one of the hottest months. The study indicated that passive solar techniques employed in the Trad.H were able to maintain the comfortable indoor environment for the occupants without any mechanical aid. The indoor temperature of the Eco.H was 3 to 9 °C higher, and the Mod.H difference was 5 to 9°C above the thermal comfort zone. The study ascertained that designs of buildings with traditional construction and material played a significant role in moderating the indoor environment when the outdoor climate of the Algerian desert was unbearable. Inadvertently, energy for cooling was saved creating a significant impact not only on the economy both at the national and global level, but on the environmental scale as well.